2021
DOI: 10.36892/ijlts.v2i1.122
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude Strategies as Pragmatic Parameter of Filipino Pre-Service Teachers’ Identity

Abstract: This study investigated the common gratitude strategies in different situations, which permeated indebtedness as a way of shaping pre-service teachers' identity.  Using a 15-item Discourse Completion Test (DCT), 22 pre-service teachers in the Province of Cavite, Philippines participated in this study.  An informal interview was conducted to validate the gathered data from the instrument used.  The analysis was done through the use of Cheng's (2005) taxonomy of gratitude expressions, which include eight (8) str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…To sum up, the findings showed that the most frequent strategies were simple thanking and appreciation. These results to some extent are similar to Salayo (2021) who found that the most usable thanking strategies used by teachers were 'simple thanking. Faqe et al (2019) also showed that the most frequently-used thanking expressions by Kurdish EFL learners were 'thanking, state of favor, and appreciation'.…”
Section: Results Related To the Study Questionsupporting
confidence: 87%
See 2 more Smart Citations
“…To sum up, the findings showed that the most frequent strategies were simple thanking and appreciation. These results to some extent are similar to Salayo (2021) who found that the most usable thanking strategies used by teachers were 'simple thanking. Faqe et al (2019) also showed that the most frequently-used thanking expressions by Kurdish EFL learners were 'thanking, state of favor, and appreciation'.…”
Section: Results Related To the Study Questionsupporting
confidence: 87%
“…The findings showed that the most frequently-used thanking expressions by Kurdish EFL learners were 'thanking, state of favor, and appreciation'. Salayo (2021) examined the most common thanking expression strategies used by pre-service teachers and showed how the identified gratitude strategies built their identity. a 15-item Discourse Completion Test (DCT) is used to collect the needed data from 22 pre-service teachers in the Province of Cavite, Philippine.…”
Section: International Journal Of English Language and Literature Stu...mentioning
confidence: 99%
See 1 more Smart Citation